VALIDATION OF LOSS GIVEN DEFAULT FOR CORPORATE - Vujnović, Miloš; Vujnović, Anja; Nikolić, Nebojša (Journal of Applied Engineering Science, 2016)
This paper presents an contemporary approach for development and validation of Loss given default(LGD) in accordance with the Basel Accords standards. The modeling data set has been based ondata on recoveries of outstanding debts from corporate entities in Republic of Serbia that defaulted.The aim of the paper is to develop a LGD model capable of confirming the validity of historically observedLGD estimates on the sample of corporate entities that defualted. The modelling approachin this research is based on average LGD without time or exposure weightening. The probabilitydensity function of realized empirical LGDs has been created by beta distribution usage. The validationprocess on proposed LGD model has been performed by throughout testing of: cumulative LGDaccuracy ratio, mean square error calculation and regression analysis. On the basis of obtainedresults, the possibilities of application of the developed LGD model are proposed and discussed.